Inhibition of PTP1B Promotes M2 Polarization via MicroRNA-26a/MKP1 Signaling Pathway in Murine Macrophages - Xu, Xiaolong; Wang, Xuerui; Guo, Yuhong; Bai, Yunjing; He, Shasha; Wang, Ning; Lin, Yan; Fisher, Marc; Liu, Qingquan; Yao, Yongming (Frontiers in Immunology, 2019)
Sepsis is a life-threatening condition often occurring in intensive care units. Excessive activation of host immune system at the early stage contributes to multiple organ damage. Mitogen-activated protein kinase phosphatase-1 (MKP1) plays a critical role in inflammatory process. In our recent bioinformatic analysis, we confirmed the notion that the inhibition of protein tyrosine phosphatase-1B (PTP1B) significantly enhances the expression of MKP1 in murine macrophages. However, the underlying mechanism remained unclear, as well as its effect on macrophage polarization. In this work, we verified that the suppression of PTP1B induced upregulation of MKP1 in M1 macrophages. A RayBiotech mouse inflammation antibody assay further revealed that MKP1-knockdown strengthened the pro-inflammatory cytokine (IL-1β, IL12p70, IL-17, IL-21, IL-23, and TNF-α) secretion but suppressed the anti-proinflammatory cytokine (IL-10) production in M2 macrophages. Phospho-proteomics analysis further identified ERK1/2 and p38 as downstream molecules of MKP1. Moreover, we found that the inhibition of PTP1B lowered the expression of miR-26a, showing a negative correlation with MKP1 protein expression. Thus, we concluded that the inhibition of PTP1B contributes to M2 macrophage polarization via reducing mir-26a and afterwards enhancing MKP1 expression in murine macrophages.